Latin American Documentary Filmmaking: Major Works - Black, Kyle K. (Imagofagia, 2021)
Sobre Foster, David William. Latin American Documentary Filmmaking: Major Works. Tucson, Arizona: The University of Arizona Press, 2013, 232 pp., ISBN-13: 978-0816523894